Study of thermal effects of silicate-containing hydroxyapatites; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Golovanova O. A.; Zaits A. V.; Berdinskaya N. V.; Mylnikova T. S. Tatyana Stepanovna (2016, 2016)
Title screen